2021
DOI: 10.3390/ma14030601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Temperature on the Fracture Properties of Polyolefin Fibre Reinforced Concrete

Abstract: Concrete has become the most common construction material, showing, among other advantages, good behaviour when subjected to high temperatures. Nevertheless, concrete is usually reinforced with elements of other materials such as steel in the form of rebars or fibres. Thus, the behaviour under high temperatures of these other materials can be critical for structural elements. In addition, concrete spalling occurs when concrete is subjected to high temperature due to internal pressures. Micro polypropylene fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Among the above-mentioned, LDPE is used to make most film packaging [9]. Interest in conventional plastics is related to well-known methods of processing these materials [10,11]. Materials intended for packaging must have appropriate processability, good durability, barrier properties and the possibility of creating multi-layer materials or additional active properties, including biocidal and biostatic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the above-mentioned, LDPE is used to make most film packaging [9]. Interest in conventional plastics is related to well-known methods of processing these materials [10,11]. Materials intended for packaging must have appropriate processability, good durability, barrier properties and the possibility of creating multi-layer materials or additional active properties, including biocidal and biostatic [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the volume fraction of the steel fiber (20%) used in this study could effectively suppress the explosive spalling induced by high temperatures, and the cross-section loss of steel fibers increased with an increase in the thermal damage. Alberti et al [15] investigated the residual fracture energy and strength of polyolefin fiber reinforced concrete (PFRC) by adopting a three-point bending test after exposure to fire at temperature ranging from 20 • C to 200 • C. Polyolefin macro fibers (PF) are known to be a viable alternative to steel fiber for structural reinforcement in specific applications. It was revealed that the degradation of the mechanical properties of PFRC occurred between 150 • C and 200 • C, and the specimens showed no structural capacity at 200 • C because most of the fibers were found to be melted.…”
Section: Introductionmentioning
confidence: 99%
“…Among those fibers, the polypropylene fiber (PF), attributing to the high abrasion and corrosion resistance and low cost, was a promising reinforcing material using in the alkaline environment where the concrete holds [ 15 , 16 , 17 ]. The PF was effectively in curbing spalling caused by internal pressure of concrete under high temperature and is beneficial for structural design of elements [ 18 ]. Owing to the high tensile strength of PF, the tensile strength and the toughness of concrete can be elevated while the plastic shrinkage and the brittleness are reduced.…”
Section: Introductionmentioning
confidence: 99%